Exploring the Impact of Educational Background and Learning Motivation on Students' Speaking Performance - Aisyahrani Arifin; Abdul Kodir; Ade Nandang (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to examine the relationship between educational background, learning motivation, and academic achievement in the Maharah Kalam (speaking skills) course among 2023 cohort students of the Arabic Language and Literature Department. The study was conducted in response to challenges in Arabic speaking proficiency, where students often understand the material but struggle to respond to questions or comments from lecturers or peers. The Maharah Kalam course is designed to enhance students' speaking abilities. This research employed a descriptive quantitative method, with a population of 207 students and a sample of 104. Data collection techniques included surveys, interviews, questionnaires, literature reviews, and tests. The questionnaire covered aspects of educational background, learning motivation, and academic performance. Data were analyzed using Pearson correlation with the help of SPSS software. The findings show a weak but positive correlation between learning motivation and academic performance (r = 0.246; p = 0.012), suggesting that increased motivation is associated with a slight improvement in performance. In contrast, the correlation between educational background and both motivation and academic performance was very weak and statistically insignificant. The R-value of 0.291 indicates a weak overall relationship among the studied variables. The combined contribution of learning motivation and educational background to academic performance was 8.5%, while other factors influenced the remaining 91.5%. This research contributes to an initial understanding of factors influencing speaking skills achievement. It is recommended that instructors develop more interactive and contextual teaching methods while considering non-academic factors such as learning environment and student self-confidence to enhance Arabic speaking proficiency effectively.